Gut microbiome dynamics of patients on dialysis: implications for complications and treatment - Li, Changlin; Lin, Xiaomeng; Li, Yuting; Duan, Jiamin; Cai, Xudong (Frontiers in Pharmacology, 2025)
The gut microbiome plays a significant role in dialysis. As disease progresses, the choice of dialysis method and dietary habits change, and the diversity and richness of the gut microbiome in patients on dialysis change as well. The uremic toxins produced exacerbate inflammatory responses and oxidative stress, leading to markedly different incidence rates of complications such as cardiovascular disease and dialysis-associated peritonitis among patients on dialysis. The intake of probiotics, prebiotics, synbiotics, and natural medicines during daily life can regulate the gut microbiome, reduce the production of uremic toxins in patients on dialysis. This review found that the occurrence of complications in dialysis patients is related to changes in the gut microbiome and the accumulation of uremic toxins. The use of probiotics, prebiotics, synbiotics, and natural medicines can improve these conditions and reduce the incidence of dialysis-related complications.